Panama 2025 - Bell, Rosie; Ver Berkmoes, Ryan; Egerton, Alex; Ruiz, Jennifer; Scott, Jesse (Lonely Planet guidebooks., 2025)
Lonely Planet's local travel experts reveal all you need to know to plan a multi-week adventure to Panama. Relax on stunning white sand beaches, dig into delicious Panamanian dishes, spot monkeys and sloths, with our classic travel guide that's packed with comprehensive itineraries, maps, and essential tips so you can create the trip of a lifetime.